A Integrating Maqashid Sharia Index (MSI) into ESG Performance in the Post-Crisis Era: Comparative Evidence from Islamic and Conventional Banks in Indonesia and Malaysia - Mahmud Syukri (IQTISHADIA Jurnal Ekonomi & Perbankan Syariah, 2025)
Bank performance measurement has long been dominated by financial indicators such as ROA, ROE, and CAR, which tend to be partial and fail to adequately reflect sustainability and Sharia compliance. This limitation highlights the need for a more holistic evaluation framework. This study aims to integrate the Maqashid Sharia Index (MSI), which represents Sharia objectives, with Environmental, Social, and Governance (ESG) as a global standard, to produce a more comprehensive performance measure. The research employs a cross-country quantitative comparative approach using panel data from Islamic and conventional banks in Indonesia and Malaysia over the period 2019–2024. Data were collected from annual and sustainability reports and analyzed using the Simple Additive Weighting (SAW) method for index assessment, along with comparative statistical tests and multivariate regression to examine the hypotheses. The findings reveal that the MSI–ESG integration provides a fairer and more holistic picture of bank performance compared to conventional financial ratios and identifies significant differences in the performance profiles of Islamic and conventional banks in both countries. This study concludes that performance measurement based on MSI–ESG integration offers a more globally relevant and Sharia-compliant alternative evaluation model.